blob: cba6f9edf3a1532d28b079cbd741f271e314abef [file] [log] [blame]
avm99963b2d45802021-04-01 01:25:24 +02001\documentclass[11pt,a4paper,dvipsnames]{article}
2\usepackage[utf8]{inputenc}
3\usepackage{lmodern}
4\usepackage{amsmath}
5\usepackage{amsfonts}
6\usepackage{amssymb}
7\usepackage{mathtools}
8\usepackage{parskip}
9\usepackage{xcolor}
10\usepackage{tcolorbox}
11\usepackage{hyperref}
12\usepackage{geometry}
13\usepackage{physics}
14\usepackage{systeme,mathtools}
15\usepackage[usestackEOL]{stackengine}
16\usepackage{scalerel}
17\usepackage{graphicx}
18\usepackage{enumerate}
19\usepackage{tikz}
20\usepackage[labelfont=bf]{caption}
21\usepackage{siunitx}
22\usepackage{cancel}
23\usepackage{fbox}
24\usepackage{multicol}
25\usepackage{amsthm}
26\usepackage[shortlabels]{enumitem}
27\usetikzlibrary{positioning}
28\geometry{top=25mm}
29
30% Plantilla per l'interior d'un conjunt
31\newcommand{\interior}[1]{%
32 {\kern0pt#1}^{\mathrm{o}}%
33}
34
35% Plantilles del notate
36\def\myupbracefill#1{\rotatebox{90}{\stretchto{\{}{#1}}}
37\def\rlwd{.5pt}
38\newcommand\notate[4][B]{%
39 \if B#1\else\def\myupbracefill##1{}\fi%
40 \def\useanchorwidth{T}%
41 \setbox0=\hbox{$\displaystyle#2$}%
42 \def\stackalignment{c}\stackunder[-6pt]{%
43 \def\stackalignment{c}\stackunder[-1.5pt]{%
44 \stackunder[2pt]{\strut $\displaystyle#2$}{\myupbracefill{\wd0}}}{%
45 \rule{\rlwd}{#3\baselineskip}}}{%
46 \strut\kern9pt$\rightarrow$\smash{\rlap{$~#4$}}}%
47}
48
49% Plantilles dels boxes
50%%%% START DEFINING LBOXED, RBOXED %%%%
51\newcommand{\lboxed}[1]{\fbox[blt]{\mathsurround=0pt$\displaystyle#1$}}
52\newcommand{\rboxed}[1]{\fbox[brt]{\mathsurround=0pt$\displaystyle#1$}}
53
54% Plantilles pels problemes
55\newcounter{problem}
56\newcounter{solution}
57
58\newcommand{\green}[1]{\textbf{\color{ForestGreen} #1}}
59
60\newcommand{\separator}{\noindent\hfil\rule{0.75\textwidth}{0.4pt}\hfil}
61
62\newenvironment{Problem}{%
63 \stepcounter{problem}%
64 \begin{tcolorbox}[colback=cyan!10!white,parbox=false]
65 \textbf{Problem \theproblem.}~%
66 \setcounter{solution}{0}}{%
67 \end{tcolorbox}
68}
69
70\newenvironment{FreeProblem}{%
71 \begin{tcolorbox}[colback=cyan!10!white,parbox=false]
72 \setcounter{solution}{0}}{%
73 \end{tcolorbox}
74}
75
76\newcommand\Solution{%
77 \textbf{Solution:}\\%
78}
79
80\newcommand\Context{%
81 \textbf{Context:}\\%
82}
83
84\newcommand\Lema{%
85 \textbf{Lema:} %
86}
87
88\newcommand\Proposition{%
89 \textbf{Proposition:} %
90}
91
92\newcommand\Theorem{%
93 \textbf{Theorem:} %
94}
95
96\newcommand\Proof{%
97 \textbf{Proof:}\\%
98}
99
100\newcommand\QED{\square}
101
102\newcommand\ASolution{%
103 \stepcounter{solution}%
104 \textbf{Solution \thesolution:}\\%
105}
106
107
108\newcommand{\asection}[2]{
109\setcounter{section}{#1}
110\addtocounter{section}{-1}
111\section{#2}
112}
113
114% Tensor commands:
115\newcommand*{\TT}[1]{\bar{\bar{#1}}}
116
117%\usepackage{biblatex}
118%\addbibresource{references.bib}
119
120\title{Homework 2\\Continuum Mechanics}
121\author{Adrià Vilanova Martínez}
122\date{March 28, 2021}
123
124\begin{document}
125
126\maketitle
127
128\begin{Problem}
129 Consider vector $\vec{a}$. Show that $\nabla \cross \vec{a} = 2 \vec{v}$, where $\vec{v}$ is the dual vector associated to the antisymmetric part of the second rank tensor $\nabla \vec{a}$.
130
131 In fluid mechanics, the tensor $\nabla \vec{v}$, with $\vec{v}$ the velocity, plays a relevant role. Its antisymmetric part contains information about the rotation of material particles. In fact, the dual vector associated to this antisymmetric part is the angular velocity of the material particle, which is half the vorticity at a point within the fluid. In elasticity, the same ideas apply with the displacement vector $\vec{u}$ playing the role of the velocity.
132\end{Problem}
133
134\Solution
135
136We know that \[ (\nabla \vec{a})_{ij} = \partial_i a_j. \]
137
138Therefore the antisymmetric part of tensor $\nabla \vec{a}$ is (component by component) \[ ((\nabla \vec{a})_A)_{ij} = \frac{1}{2} ((\nabla \vec{a})_{ij} - (\nabla \vec{a})_{ji}) = \frac{1}{2} (\partial_i a_j - \partial_j a_i). \]
139
140Finally, its associated dual vector multiplied by 2 ($2 \vec{v}$) will be, by definition of the dual vector: \[ \begin{cases}
141 2 v_x = 2 ((\nabla \vec{a})_A)_{yz} = \partial_y a_z - \partial_z a_y \\
142 2 v_y = 2 ((\nabla \vec{a})_A)_{zx} = \partial_z a_x - \partial_x a_z \\
143 2 v_z = 2 ((\nabla \vec{a})_A)_{xy} = \partial_x a_y - \partial_y a_x.
144\end{cases} \]
145
146Now, we also know that
147\[ ( \nabla \cross \vec{a} )_i = \varepsilon_{ijk} \partial_j a_k, \]
148from which we obtain the same components of twice the dual vector:
149\[ \begin{cases}
150 (\nabla \cross \vec{a})_x = \partial_y a_z - \partial_z a_y \\
151 (\nabla \cross \vec{a})_y = \partial_z a_x - \partial_x a_z \\
152 (\nabla \cross \vec{a})_z = \partial_x a_y - \partial_y a_x.
153\end{cases} \]
154
155Thus, $\nabla \cross \vec{a} = 2 \vec{v}$.
156
157\begin{Problem}
158 Consider Lautrup's appendix D, which you can find posted as a pdf in ``campus virtual''.
159
160 \begin{enumerate}[a)]
161 \item Write down the $\phi\phi$-component of $\nabla \vec{a}$ in the cylindrical basis.
162 \item Write down the $\phi\theta$-component of $\nabla \vec{a}$ in the spherical basis.
163 \item Write down the $\phi$-component of $\nabla \cdot \TT{T}$, with $\TT{T}$ a second rank tensor, in the cylindrical basis.
164 \item The Laplacian of a vector $\vec{a}$ in the Cartesian basis is \\ $\nabla^2 \vec{a} = \nabla \cdot \nabla \vec{a} = \left( \partial_{xx} a_x + \partial_{yy} a_x + \partial_{zz} a_x \right) \hat{e}_x + \left( \partial_{xx} a_y + \partial_{yy} a_y + \partial_{zz} a_y \right) \hat{e}_y + \\ + \left( \partial_{xx} a_z + \partial_{yy} a_z + \partial_{zz} a_z \right) \hat{e}_z$. Using index notation, the $k$ component is $\partial_i \partial_j a_k$. Look at the Laplacian expression in the cylindrical and spherical bases. There are additional terms compared to those in the Cartesian basis. Very briefly explain why this is the case.
165 \end{enumerate}
166\end{Problem}
167
168\textbf{Solution for a):}
169\[ (\nabla \vec{a})_{\phi\phi} = \frac{1}{r} (\partial_\phi a_\phi + a_r) \]
170
171\textbf{Solution for b):}
172\[ (\nabla \vec{a})_{\phi \theta} = \frac{1}{r \sin \theta} \partial_\phi a_\theta - \frac{a_\phi}{r \tan \theta} \]
173
174\textbf{Solution for c):}
175\[ \nabla \cdot \TT{T} = \nabla_i T_{ij} \hat{e}_j \implies (\nabla \cdot \TT{T})_\phi = \partial_r T_{r \phi} + \frac{1}{r} \partial_\phi T_{\phi \phi} + \partial_z T_{z \phi} + \frac{1}{r} T_{\phi r} + \frac{1}{r} T_{r \phi} \]
176
177\textbf{Solution for d):}
178
179There are additional terms in the Laplacian expression in cylindrical and spherical bases because of the fact that the del operator ($\nabla$) in those other bases is developed by applying the chain rule to the expresion in cartesian coordinates (which introduces ``complexity'' to the operator) and when calculating the second partial derivatives in order to express the Laplacian, all the basis vectors are no longer constant (their spatial variation matters), as opposed to the natural (cartesian) basis.
180
181\begin{Problem}
182 In class, we have considered material particles subjected to normal and shear forces in mechanical equilibrium. Translational equilibrium requires $\sum \vec{F} = 0$. Assuming the stress tensor is symmetric guarantees that the total torque or momentum of force is $\vec{M} = 0$.
183
184 In this problem we are going to look at this a bit more carefully; we will clearly see that choosing $\TT{\sigma}$ symmetric is one (very good) option, but that, in general, $\TT{\sigma}$ does not need to be symmetric. We will also practice with index notation adn tensor calculus. As usual, use summation convention.
185
186 \begin{enumerate}[a)]
187 \item The total moment of force is \[ \vec{M} = \int_V \vec{x} \cross d\vec{F} = \int_V \vec{x} \cross \vec{f^*} dV' \] where $\vec{f^*}$ is the total specific (per volume) force, including body and contact forces.
188
189 Show that the i-component of $\vec{M}$ is \[ M_i = \int_v \varepsilon_{ijk} x_j (f_k + \partial_l \sigma_{kl}) dV' \] where $f_k$ is the k-component of the body force.
190
191 \item Then, show that \[ M_i = \int_V \varepsilon_{ijk} (x_j f_k + \partial_l (x_j \sigma_{kl}) - \sigma_{kj}) dV'. \]
192
193 \item Use Gauss's theorem to show that \[ \int_V \varepsilon_{ijk} \partial_l(x_j \sigma_{kl}) dV' = \oint_A (\vec{x} \cross \TT{\sigma} \cdot d\vec{S})_i. \]
194
195 \item Now, realize $- \varepsilon_{ijk} \sigma_{kj} = \varepsilon_{ijk} \sigma_{jk}$.
196 \end{enumerate}
197
198 Using the results in (c) and (d), we then have: \[ \vec{M} = \int_V \vec{x} \cross \vec{f} dV' + \oint_A \vec{x} \cross \TT{\sigma} \cdot d\vec{S} + \int_v \hat{e}_i \varepsilon_{ijk} \sigma_{jk} dV'. \]
199
200 In the absence of body forces, taking $\TT{\sigma}$ symmetric guarantees that $\vec{M} = 0$. In this case, we showed in class that the second term is zero. The third term is also zero, since a permutation of indices $j, k$ changes the sign in $\varepsilon_{ijk}$.
201
202 However, $\vec{M} = 0$ does not require $\TT{\sigma}$ to be symmetric. In the absence of body forces, only the sum of the 2nd and 3rd tirms in $\vec{M}$ must vanish. There are, in fact, generalizations of classical continuum theory that use non-symmetric stress tensors. In classical continuum theory, however, we choose $\TT{\sigma}$ symmetric and develop a coherent theory with this selection.
203\end{Problem}
204
205\newpage
206
207\textbf{Solution for a):}
208\[ M_i = \left( \int_V \vec{x} \cross \vec{f^*} dV' \right)_i = \int_V (\vec{x} \cross \vec{f^*})_i \, dV' \notate[X]{{}={}}{1.25}{\scriptstyle (\vec{B} \cross \vec{C})_i = \varepsilon_{ijk} B_j C_k} \int_V \varepsilon_{ijk} x_j f^*_k \, dV' \notate[X]{{}={}}{1.25}{\scriptstyle f^*_i := f_i + \partial_j \sigma_{ij}} \int_V \varepsilon_{ijk} x_j (f_k + \partial_l \sigma_{kl}) \, dV' \]
209
210\textbf{Solution for b):}
211
212We must show that $\varepsilon_{ijk} x_j \partial_l \sigma_{kl} = \varepsilon_{ijk} (\partial_l (x_j \sigma_{kl}) - \sigma_{kj})$.
213
214If we take into account that $\vec{x} = (x, y, z)$, then $\partial_i x_j = \delta_{ij}$, then it is clear that \[ \varepsilon_{ijk} (\partial_l (x_j \sigma_{kl}) - \sigma_{kj}) = \varepsilon_{ijk} ((\partial_l x_j) \sigma_{kl} + x_j (\partial_l \sigma_{kl}) - \sigma_{kj}) = \varepsilon_{ijk} (\delta_{lj} \sigma_{kl} + x_j (\partial_l \sigma_{kl}) - \sigma_{kj}) = \]
215\[ = \varepsilon_{ijk} (\sigma_{kj} + x_j (\partial_l \sigma_{kl}) - \sigma_{kj}) = \varepsilon_{ijk} x_j (\partial_l \sigma_{kl}). \]
216
217\textbf{Solution for c):}
218
219Gauss's theorem in general states that
220\[ \int_V \partial_l T_{jkl} \, dV' = \oint_A T_{jkl} n_l \, dS. \]
221
222In our case, if we take $T_{jkl} = x_j \sigma_{kl}$, we get:
223\[ \int_V \partial_l (x_j \sigma_{kl}) \, dV' = \oint_A x_j \underbrace{\sigma_{kl} n_l \, dS}_{= (\TT{\sigma} \cdot \vec{dS})_k} \implies \]
224\[ \implies \int_V \varepsilon_{ijk} \partial_l (x_j \sigma_{kl}) \, dV' = \oint_A \underbrace{\varepsilon_{ijk} x_j (\TT{\sigma} \cdot \vec{dS})_k}_{= (\vec{x} \cross \TT{\sigma} \cdot \vec{dS})_i} \implies \]
225\[ \implies \int_V \varepsilon_{ijk} \partial_l (x_j \sigma_{kl}) \, dV' = \oint_A (\vec{x} \cross \TT{\sigma} \cdot \vec{dS})_i. \]
226
227\textbf{Solution for d):}
228
229If two of more of $\{i, j, k\}$ are equal, then this is trivial.
230
231Otherwise, consider the permutation $(i, j, k)$. Then $(i, j, k)(j, k) = (i, k, j)$ has the opposite sign of the original permutation, since we have transposed 2 elements of the permutation. Since $\varepsilon_{ijk}$ gives us the sign of the permutation, this means $- \varepsilon_{ijk} = \varepsilon_{ikj}$.
232
233Thus, we have: \[ -\varepsilon_{ijk} \sigma_{kj} = \varepsilon_{ikj} \sigma_{kj} \]
234
235Since $\{j, k\}$ are the indices we are summing over, we can change their names (in particular swap them) and the result will be the same. In conclusion:
236\[ \varepsilon_{ikj} \sigma_{kj} = \varepsilon_{ijk} \sigma_{jk} \]
237which proves the statement.
238
239\begin{Problem}
240 Consider a rigid body rotation through angle $\phi$ around the z-axis. In matrix form: \[ \begin{pmatrix}
241 x' \\
242 y' \\
243 z'
244 \end{pmatrix} = \begin{pmatrix}
245 \cos \phi & - \sin \phi & 0 \\
246 \sin \phi & \cos \phi & 0 \\
247 0 & 0 & 1
248 \end{pmatrix} \begin{pmatrix}
249 x \\
250 y \\
251 z
252 \end{pmatrix}. \]
253
254 Note this rotation matrix is not the one associated to a rotation of axes, which we call a passive rotation. In the case considered here, the basis remains the same; it is the vector that is rotated by angle $\phi$. We call this an active rotation.
255
256 Note also that the matrix above is the inverse of the matrix associated to a rotation of axes by angle $\phi$ around the z-axis. You can easily visualize that an active rotation by angle $\phi$ followed by a passive rotation of axes by the same angle $\phi$ leaves the vector unchanged. Hence the matrices representing active and passive rotations are inverses of one another; since the transformations are orthogonal, we can also say they are transposes of one another.
257
258 \begin{enumerate}[a)]
259 \item Find the displacement field induced by the active rotation above.
260 \item Find $\text{grad}\, \vec{u} = (\nabla \vec{u})^T$.
261 \item Remember that $d\vec{r'} = d\vec{r} + \text{grad}\, \vec{u} \cdot d\vec{r}$. Confirm that $|d\vec{r'}| = |d\vec{r}|$; this indicates there is no deformation of the body.
262 \item Confirm the strain tensor $\TT{u} = 0$ (you will need to use the full expression for $\TT{u}$; not Cauchy's strain tensor).
263 \end{enumerate}
264
265 Note: for slowing varying displacement fields, the angle $\phi$ is small, and to leading order, $\text{grad}\, \vec{u} = (\nabla \vec{u})^T$ becomes antisymmetric. This connects to what we said in class: For $\displaystyle \left| \frac{\partial u_i}{\partial x_k} \right| \ll 1$, $\text{grad}\, \vec{u} = \TT{u} + \TT{w}$, where $\TT{u}$ is Cauchy's strain tensor and $\TT{w}$ is an antisymmetric tensor related to the rotation of material particles. In this problem, since there is no deformation, for small $\phi$, $\text{grad}\, \vec{u} = \TT{w}$.
266\end{Problem}
267
268\textbf{Solution for a):}
269\[ \vec{u}(\vec{r}) = \vec{r'} - \vec{r} = \begin{pmatrix}
270 \cos \phi - 1 & - \sin \phi & 0 \\
271 \sin \phi & \cos \phi - 1 & 0 \\
272 0 & 0 & 0
273\end{pmatrix} \begin{pmatrix}
274 x \\
275 y \\
276 z
277\end{pmatrix} = \begin{pmatrix}
278 (\cos \phi - 1) \cdot x - \sin \phi \cdot y \\
279 \sin \phi \cdot x + (\cos \phi - 1) \cdot y \\
280 0
281\end{pmatrix} \]
282
283\textbf{Solution for b):}
284\[ \text{grad}\, \vec{u} = \begin{pmatrix}
285 \cos \phi - 1 & - \sin \phi & 0 \\
286 \sin \phi & \cos \phi - 1 & 0 \\
287 0 & 0 & 0
288\end{pmatrix} \]
289
290\textbf{Solution for c):}
291\[ d\vec{r'} = d\vec{r} + \text{grad}\, \vec{u} \cdot d\vec{r} = (Id + \text{grad}\, \vec{u}) \cdot d\vec{r} \implies \]
292\[ \implies | d\vec{r'} | = | (Id + \text{grad}\, \vec{u}) \cdot d\vec{r} | = \left| \begin{pmatrix}
293 \cos \phi & - \sin \phi & 0 \\
294 \sin \phi & \cos \phi & 0 \\
295 0 & 0 & 1
296\end{pmatrix} d\vec{r} \right| = \left| \begin{pmatrix}
297 \cos \phi \cdot dr_x - \sin \phi \cdot dr_y \\
298 \sin \phi \cdot dr_x + \cos \phi \cdot dr_y \\
299 dr_z
300\end{pmatrix} \right| = \]
301\[ = \sqrt{(\cos \phi \cdot dr_x - \sin \phi \cdot dr_y)^2 + (\sin \phi \cdot dr_x + \cos \phi \cdot dr_y)^2 + dr_z^2} = \]
302\[ = \sqrt{(\sin^2 \phi + \cos^2 \phi) dr_x^2 + (\sin^2 \phi + \cos^2 \phi) dr_y^2 + dr_z^2} = \]
303\[ = \sqrt{dr_x^2 + dr_y^2 + dr_z^2} = |dr| \]
304
305\textbf{Solution for d):}
306
307We could show that each component is zero, by using the following expression: \[ u_{ik} = \frac{1}{2} \left[ \frac{\partial u_i}{\partial x_k} + \frac{\partial u_k}{\partial x_i} + \sum_l \frac{\partial u_l}{\partial x_i} \cdot \frac{\partial u_l}{\partial x_k} \right] \]
308
309However, we know from the definition of the strain tensor that \[ | d\vec{r'} |^2 = | d\vec{r} |^2 + 2 \sum_{i, k} u_{ik} \, dx_i dx_k \] and since we have shown that $| d\vec{r'} |^2 = | d\vec{r} |^2$, we have that \[ \sum_{i, k} u_{ik} \, dx_i dx_k = 0 \] and since $\{ dx_i dx_k \}_{i, k}$ are linearly independent, we have that \[ u_{ik} = 0 \quad \forall i, k \] which means that $\TT{u} = 0$.
310
311\begin{Problem}
312 \begin{enumerate}[a)]
313 \item In class, we have considered the homogeneous (also called uniform) stretching along the x-direction of a solid clamped on its left-most side and having an equilibrium length along this direction equal to $L$.
314
315 Write down Cauchy's strain tensor, knowing that the stretch of the right-most point of the solid is $\Delta L$.
316
317 \item Consider the \textit{pure shear} deformation of the solid considered in class (see Fig. 1).
318
319 Write down Cauchy's strain tensor (assume small deformations as we did in class).
320
321 \item Now consider a \textit{simple shear} deformation (see Fig. 2). Write down the second rank tensor $\text{grad}\, \vec{u} = (\nabla \vec{u})^T$, for small $\theta$. You will see it is not symmetric.
322
323 Obtain the symmetric and antisymmetric parts. Realize that the symmetric part is Cauchy's strain tensor.
324
325 The antisymmetric part informs about rotations of material particles. Since it is a second rank tensor, we have a dual vector we can associate to it, which we know is related to $\nabla \cross \vec{u}$. We then see we can think of rotations in terms of the antisymmetric part of $\text{grad}\, \vec{u}$ (or $\nabla \vec{u}$), or in terms of the vector $\nabla \cross \vec{u}$.
326 \end{enumerate}
327\end{Problem}
328
329\textbf{Solution for a):}
330
331Homogenous stretching along the x-direction keeping the left-most side clamped means that \[ \vec{r'} = \begin{pmatrix}
332 k x \\
333 y \\
334 z
335\end{pmatrix} \] where $k \in \mathbb{R}$ is a constant.
336
337Therefore: \[ \vec{u}(\vec{r}) = \vec{r'} - \vec{r} = \begin{pmatrix}
338 (k - 1) x \\
339 0 \\
340 0
341\end{pmatrix}. \]
342
343We have \[ \text{grad}\, \vec{u} = \begin{pmatrix}
344 k - 1 & 0 & 0 \\
345 0 & 0 & 0 \\
346 0 & 0 & 0
347\end{pmatrix} \] and this lets us calculate Cauchy's strain tensor:
348\[ \TT{u} = \frac{1}{2} (\text{grad}\, \vec{u} + (\text{grad}\, \vec{u})^T) \notate[X]{{}={}}{1}{\scriptstyle \text{grad}\, \vec{u} \text{ is symmetric}} \text{grad}\, \vec{u} \]
349
350Since $\Delta L = (k - 1) L$, we have that $k - 1 = \frac{\Delta L}{L}$, and thus: \[ \TT{u} = \begin{pmatrix}
351 \frac{\Delta L}{L} & 0 & 0 \\
352 0 & 0 & 0 \\
353 0 & 0 & 0
354\end{pmatrix} \]
355
356\textbf{Solution for b):}
357
358In questions b) and c) we will ignore the third dimension, due to the fact that the displacement there is 0, and therefore the gradient of the displacement vector and Cauchy's strain tensor are zero in that direction.
359
360The application that gives $\vec{r'}$ as a function of $\vec{r}$ (the \textit{simple shear} deformation) is a linear application $A$ that satisfies
361\[ \begin{cases}
362 A(e_1) = e_1 + \tan\left(\frac{\theta}{2}\right) e_2 \\
363 A(e_2) = \tan\left(\frac{\theta}{2}\right) e_1 + e_2.
364\end{cases} \]
365
366Therefore: \[ \vec{r'} = A \vec{r} \quad \text{where} \quad A = \begin{pmatrix}
367 1 & \tan\left(\frac{\theta}{2}\right) \\
368 \tan\left(\frac{\theta}{2}\right) & 1
369\end{pmatrix} \] and \[ \vec{u}(\vec{r}) = \vec{r'} - \vec{r} = \begin{pmatrix}
370 0 & \tan\left(\frac{\theta}{2}\right) \\
371 \tan\left(\frac{\theta}{2}\right) & 0
372\end{pmatrix} \vec{r} \; \approx \; \begin{pmatrix}
373 0 & \frac{\theta}{2} \\
374 \frac{\theta}{2} & 0
375\end{pmatrix} \vec{r} = \frac{\theta}{2} \begin{pmatrix}
376 y \\
377 x
378\end{pmatrix}. \]
379
380Let's calculate the gradient of the displacement vector in order to calculate the strain tensor: \[ \text{grad}\, \vec{u} = \frac{\theta}{2} \begin{pmatrix}
381 0 & 1 \\
382 1 & 0
383\end{pmatrix}. \]
384
385Due to the fact that it is a symmetrical second-rank tensor, we conclude that the strain tensor is \[ \TT{u} = \frac{1}{2} (\text{grad}\, \vec{u} + (\text{grad}\, \vec{u})^T) = \text{grad}\, \vec{u} \]
386
387\textbf{Solution for c):}
388
389In this case the application $B$ which gives $\vec{r'}$ as a function of $\vec{r}$ is also linear, and satisfies
390\[ \begin{cases}
391 B(e_1) = e_1 \\
392 B(e_2) = \tan(\theta) e_1 + e_2.
393\end{cases} \]
394
395Therefore: \[ \vec{r'} = B \vec{r} \quad \text{where} \quad B = \begin{pmatrix}
396 1 & \tan(\theta) \\
397 0 & 1
398\end{pmatrix} \] and \[ \vec{u}(\vec{r}) = \vec{r'} - \vec{r} = \begin{pmatrix}
399 0 & \tan(\theta) \\
400 0 & 0
401\end{pmatrix} \vec{r} \; \approx \; \begin{pmatrix}
402 0 & \theta \\
403 0 & 0
404\end{pmatrix} \vec{r} = \begin{pmatrix}
405 \theta y \\
406 0
407\end{pmatrix}. \]
408
409At this point we can calculate the gradient of the displacement vector: \[ \text{grad}\, \vec{u} = \begin{pmatrix}
410 0 & \theta \\
411 0 & 0
412\end{pmatrix} \] which is not symmetric if $\theta \neq 0$.
413
414Let's get the symmetric and antisymmetric parts: \[ \begin{cases}
415 \displaystyle (\text{grad}\, \vec{u})_S = \frac{1}{2} \left( \text{grad}\, \vec{u} + (\text{grad}\, \vec{u})^T \right) = \frac{\theta}{2} \begin{pmatrix}
416 0 & 1 \\
417 1 & 0
418 \end{pmatrix} \\
419 \displaystyle (\text{grad}\, \vec{u})_A = \frac{1}{2} \left( \text{grad}\, \vec{u} - (\text{grad}\, \vec{u})^T \right) = \frac{\theta}{2} \begin{pmatrix}
420 0 & 1 \\
421 -1 & 0
422 \end{pmatrix}.
423\end{cases} \]
424
425As we saw in theory, Cauchy's strain tensor is defined as $\TT{u} := \frac{1}{2} \left( \nabla \vec{u} + (\nabla \vec{u})^T \right)$, so the antisymmetric part of the gradient is indeed Cauchy's strain tensor, due to the fact that $\nabla \vec{u} = (\text{grad}\, \vec{u})^T$.
426
427\newpage
428
429\begin{Problem}
430 Consider the displacement field $\vec{u} = (Ax + Cy, Cx - By, 0)$, where $A$, $B$, $C$ are small constants.
431
432 \begin{enumerate}[a)]
433 \item Compute Cauchy's strain tensor.
434 \item Find a condition to ensure that the volume remains constant.
435 \item Determine, in this case, the principal strain axes and the relative length change along the principal directions.
436 \end{enumerate}
437\end{Problem}
438
439\textbf{Solution for a):}
440\[ \text{grad}\, \vec{u} = \begin{pmatrix}
441 A & C & 0 \\
442 C & -B & 0 \\
443 0 & 0 & 0
444\end{pmatrix} \]
445\[ \TT{u} \notate[X]{{}={}}{1}{\scriptstyle \text{grad}\, \vec{u} \text{ is symmetric}} \text{grad}\, \vec{u} \]
446
447\textbf{Solution for b):}
448In theory class we saw that when the deformation is small enough, one condition to have incompressibility is that $\nabla \cdot \vec{u} = 0$. In this particular case, this gives us the following condition: \[ A - B = 0 \implies A = B. \]
449
450\textbf{Solution for c):}
451Let's find the principal strain axes (which correspond to the eigenvectors of $\TT{u}$):
452
453A trivial eigenvector is $\hat{e}_z$ with associated eigenvalue $0$, since $\TT{u} \cdot \hat{e}_z = 0$
454
455Let's find the eigenvalues with the following equation: \[ \det (\TT{u} - \lambda \TT{I}) = 0 \iff 0 = \det \begin{pmatrix}
456 A - \lambda & C & 0 \\
457 C & - B - \lambda & 0 \\
458 0 & 0 & - \lambda
459\end{pmatrix} = - \lambda ((A - \lambda)(- B - \lambda) - C^2) \iff \]
460\[ \iff \begin{cases}
461 \lambda = 0, \text{ or} \\
462 (A - \lambda)(- B - \lambda) - C^2 = 0 \iff \lambda^2 - (A - B) \lambda - AB - C^2 = 0 \iff
463\end{cases} \]
464\[ \iff \lambda_\pm = \frac{A - B \pm \sqrt{A^2 + B^2 - 2AB - 4(- AB - C^2)}}{2} = \]
465\[ = \frac{1}{2} \left( A - B \pm \sqrt{(A + B)^2 + 4 C^2} \right). \]
466
467$\lambda = 0$, $\lambda_+$ and $\lambda_-$ are the principal strain values, and if we suppose $A = B$ (the condition we found for volume to be conserved) we have
468\[ \lambda_\pm = \pm \frac{1}{2} \sqrt{(2A)^2 + 4C^2} = \pm \sqrt{A^2 + C^2} \]
469and their corresponding directions are given by the following equations:
470\[ \begin{cases}
471 (\TT{u} - \lambda_+ \TT{I}) v_+ = 0 \iff \begin{pmatrix}
472 A - \sqrt{A^2 + C^2} & C & 0 \\
473 C & - A - \sqrt{A^2 + C^2} & 0 \\
474 0 & 0 & - \sqrt{A^2 + C^2}
475 \end{pmatrix} v_+ = 0 \iff \\
476 \iff [ v_+ ] = \left[ \begin{pmatrix}
477 - \frac{C}{A - \sqrt{A^2 + C^2}}, & 1, & 0
478 \end{pmatrix} \right] \\ \\
479 \hline \\
480 (\TT{u} - \lambda_- \TT{I}) v_- = 0 \iff \begin{pmatrix}
481 A + \sqrt{A^2 + C^2} & C & 0 \\
482 C & - A + \sqrt{A^2 + C^2} & 0 \\
483 0 & 0 & \sqrt{A^2 + C^2}
484 \end{pmatrix} v_- = 0 \iff \\
485 \iff [ v_- ] = \left[ \begin{pmatrix}
486 - \frac{C}{A + \sqrt{A^2 + C^2}}, & 1, & 0
487 \end{pmatrix} \right]
488\end{cases} \]
489
490%\printbibliography
491
492\end{document}